A gamebook enriched with the literary past – an analysis of the paragraph game “Dziady Część V. Dziady, które nie spieprzają” by Mikołaj Kołyszko - Sowa, Julia (Replay. The Polish Journal of Game Studies, 2023)
This article addresses issues showing the interconnectedness of the postmodern categories of pastiche and parody in relation to gamebooks. The first part of the text is a cross-section of the most important theoretical issues for the subsequent analysis of the gamebooks, starting with the presentation of their definitions, the most popular genres, and the basic division of such games. In relation to the issue of gamebooks, I also draw attention to the increasing intermediality of the contemporary works, as well as the importance of second-person narration. I also mention the genre of art games and briefly cite the work of one of their representatives, Anna Anthropy. I then discuss the postmodern categories of pastiche and parody and what they mean in relation to the past-present relationship. In the context of parody, I also mention Gérard Genette’s division of transtextual references between works. All the above-mentioned issues will be referred to when analysing the gamebook, which is a ‘semi-official’ continuation of Mickiewicz’s Dziady, combining a parodic take on folk culture with contemporary new media elements.